2014
DOI: 10.1111/aji.12341
|View full text |Cite
|
Sign up to set email alerts
|

Purified IgG from Patients with Obstetric but not IgG from Non‐obstetric Antiphospholipid Syndrome Inhibit Trophoblast Invasion

Abstract: ProblemSome patients with antiphospholipid syndrome (APS) suffer pregnancy morbidity (PM) but not vascular thrombosis (VT), whilst others suffer VT only. Therefore, we compared the effects of IgG from VT+/PM− and VT−/PM+ subjects on human first-trimester trophoblast (HTR8) cells.Method of studyHTR-8 cells were incubated with APS VT+/PM−, APS VT−/PM+ or healthy control (HC) IgG. We measured trophoblast invasion by cell invasion assay; mRNA expression of TLR4 and adaptor proteins; phosphorylation of p38 MAPK, NF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 39 publications
3
23
0
Order By: Relevance
“…These results were in concordance with a recently published report by Poulton et al. using polyclonal IgG antibodies from patients with APS . Although the FAK pathway is involved in cellular migration and is activated in HTR‐8/SVneo cells (revised in), in our hands no changes were induced by either polyclonal IgGs or other drugs (data not shown).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These results were in concordance with a recently published report by Poulton et al. using polyclonal IgG antibodies from patients with APS . Although the FAK pathway is involved in cellular migration and is activated in HTR‐8/SVneo cells (revised in), in our hands no changes were induced by either polyclonal IgGs or other drugs (data not shown).…”
Section: Discussionsupporting
confidence: 94%
“…We have previously demonstrated that pooled sera from patients with APS impair trophoblast migration . Hence, here we evaluated the effect of IgGs purified from these pooled sera on trophoblast invasion and found that our results agree with previous reports using polyclonal IgG antibodies obtained from patients with APS, demonstrating aPL‐induced reduction in trophoblast cell invasion. The next step was to evaluate the effects of drugs currently used to prevent pregnancy complications associated with APS such as low‐molecular‐weight heparin (LMWH) and aspirin because several studies have suggested that they may exert direct effects on placental trophoblast cells, independently of their antithrombotic activity .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Heparan sulfate, Toll-like receptors 2 and 4, apolipoprotein E receptor 2, and annexin II that are expressed by trophoblasts and decidual cells are the main candidate receptors for β2GPI identified by in vitro studies [62]. In particular, apolipoprotein E receptor 2 has been suggested to be the key molecule mediating trophoblast dysfunction in a mouse model [64], and Tolllike receptor 4 has been demonstrated to mediate the in vitro inhibition of trophoblast invasion induced by purified aPL IgG from patients with OAPS but not by aPL IgG from non-OAPS [65].…”
Section: Obstetrical Aps Pathogenesismentioning
confidence: 99%
“…Even though the syndrome was initially described as a single disorder, the distinction between obstetric (ob-APS) and thrombotic APS has been well established during the last 10 years given the following observations: (1) patients can display vascular thrombosis with no pregnancy complications or, alternatively, obstetric manifestations alone [2]; (2) the coexistence of both thrombosis and miscarriages only affects about 2.5-5% of APS pregnancies [3]; (3) IgG fractions from pure ob-APS display different effects in vitro on monocyte and trophoblast cells [4].…”
Section: Introductionmentioning
confidence: 99%